Factors influencing willingness to pay for improved solid waste collection services among households in urban cities in Uganda: empirical evidence from Lira City - Everline Apio; Bosco Opio; Alfred Acanga; Anne Ruth Akello (BMC, 2024)
Abstract Waste management in Lira City, Uganda faces significant challenges, particularly in the area of waste collection. Pollution and health risks from uncollected waste are rampant, posing serious threats to human health and the environment. This persistent problem demands urgent attention and effective solutions to improve waste collection and safeguard the well-being of the community and the natural surroundings. This study aimed to assess households' willingness to pay for improved waste collection services, examine their waste management practices, and identify influencing factors. We employed a multistage sampling technique to randomly select 585 household heads and conducted key informant interviews with city officials and private waste collectors. Data analysis was conducted with STATA 17 and results showed that 48.12% of households were willing to pay an average of UGX 3012 ($0.84) per month for better services. Factors including education level, occupation, distance to waste collection sites, and environmental awareness significantly influenced this willingness. The study highlights a significant gap in public awareness and understanding of efficient solid waste management practices and concludes that enhancing public awareness is crucial for improving environmental health and safety in Lira City.